MANAJEMEN PEMBELAJARAN INKLUSIF - Mia Fitriani Astuti; Teti Berliani; Piter Joko Nugroho (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
This study aims to describe the Management of Inclusive Learning at SDIT Sahabat Alam Palangka Raya. This study used a qualitative approach with case study design. Sources of data for this research i.e. the Principal, LSC Coordinator, Class Teacher, Assistant Teacher, and Parents of students with special needs. Collecting data using interview, observation and documentation methods. Data analysis uses an interactive model from Miles, Huberman & Saldana (2014). Validation of data using triangulation of sources and techniques. The results of this study showed that the management of inclusive learning implemented at SDIT Palangka Raya is quite effective in providing educational services as well as developing the potential, interests, and talents of inclusive students. The success of SDIT Sahabat Alam Palangka Raya in managing and implementing inclusive learning has made that public elementary school with the nature model/concept as a reference for the people of Palangka Raya City to obtain educational services for students with special needs.